Essential oil composition of Artemisia annua L. at different growth stages - S Maiti, V S Rana, K Abirami, M A Blázquez, (Journal of Spices and Aromatic Crops, 2013)
Chemical composition of the essential oils obtained from the aerial parts of Artemisia annua at vegetative, pre-bloom, bloom and post-bloom stages was determined using GC and GC/MS analysis. The yields of essential oil were 0.14%, 0.34%, 0.64% and 0.54% (w/w), respectively at different growth stages. A total of 67 compounds were identified. Oxygenated monoterpenes (39.0%–57.0%) constituted the main fraction of the oils followed by sesquiterpene hydrocarbons (11.8%–26.2%) and monoterpene hydrocarbons (4.2%–15.1%). The main compounds identified in all the analyzed samples were camphor (28.6%–31.7%), 1,8-cineole (2.1%–20.8%), germacrene D (3.8%–12.0%), β-caryophyllene (2.8%–6.9%), trans-β-farnesene (0.7%–4.5%), α-pinene (0.5%–2.4%), p-cymene (0.8%–2.3%) and terpinen-4-ol, (0.9%–2.1%). The results indicated considerable quantitative variations in both oil yield and chemical composition at different growth stages and artemisia ketone and artemisia alcohol were found to be absent in the oils.